2010
DOI: 10.1007/s10961-010-9179-2
|View full text |Cite
|
Sign up to set email alerts
|

R&D subsidy games: a cost sharing approach vs. reward for performance

Abstract: This paper investigates government subsidy games for private sector research and development (R&D) in a two-country two-firm intra-industry trade model. Two funding structures are compared: ''cost sharing'' vs. ''reward for performance.'' Both the theoretical evidence and the results of a Monte Carlo simulation suggest that cost sharing is associated with higher social surplus and quality improvement because it prompts the firm to do more R&D. In a cost sharing program government and firm R&D are always comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…At present, CS has received some attention in academia as a means of alleviating pressure on capital costs. Existing studies have addressed various cost-sharing such as advertising inputs [39][40][41][42], R&D costs [12,43], and carbon reduction costs. In particular, in terms of carbon reduction costs, Dai et al [44] compared two cooperative models, cartel and costsharing, in an upstream manufacturer-led green supply chain, and found that the cost-sharing cooperative model could be more profitable for players and lead to peak profits across the supply chain.…”
Section: Literature Reviewmentioning
confidence: 99%
“…At present, CS has received some attention in academia as a means of alleviating pressure on capital costs. Existing studies have addressed various cost-sharing such as advertising inputs [39][40][41][42], R&D costs [12,43], and carbon reduction costs. In particular, in terms of carbon reduction costs, Dai et al [44] compared two cooperative models, cartel and costsharing, in an upstream manufacturer-led green supply chain, and found that the cost-sharing cooperative model could be more profitable for players and lead to peak profits across the supply chain.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many firms hope to obtain R&D financial subsidies from the government instead of producing high-quality R&D, and innovation outcomes, which would send a false signal of actively implementing technological innovation to the outside world. That would inhibit the company's high-quality, independent innovation R&D activities, crowding out the company's independent R&D input [31,32]. Government subsidies would stimulate the demand for relevant production factors, leading to higher prices of production factors (such as the wage cost of R&D talents), which would increase the cost of R&D input, and also inhibit the willingness of enterprises to innovate, create a crowding-out effect on corporate R&D input [33].…”
Section: A Government Innovation Support and Enterprise Randd Inputmentioning
confidence: 99%
“…The effectiveness of subsides in stimulating more R&D has been the topic of several scholarly papers [3][4][5][6][7]. Spencer and Brander [8] presented a theory of government intervention which provides an explanation for industrial strategy policy such as R&D or export subsidies in imperfectly competitive international markets.…”
Section: Introductionmentioning
confidence: 99%
“…Shin and Kim [6] analyzed the effect of government subsidy policies on creating an incentive for domestic firms to improve their product quality before exporting to an outside market. Gretz et al [4] investigated government subsidy games for private sector research and development in a two-country twofirm intraindustry trade model and compared two funding structures: cost sharing and reward for performance.…”
Section: Introductionmentioning
confidence: 99%